Chronic Cold Exposure Leads to Daytime Preference in the Circadian Expression of Hepatic Metabolic Genes - Zhang, Zhida; Cheng, Le; Ma, Junxian; Wang, Xiaomei; Zhao, Yingying (Frontiers in Physiology, 2022)
Circadian control allows organisms to anticipate and adapt to environmental changes through changes in physiology and behavior. The circadian system timing is entrained by cues, such as light, food and temperature. Ambient temperature dramatically impacts the sleep-wake cycle and metabolic rhythmicity. As endotherms, mammals rely on tissues such as the liver to provide fuel thermogenesis to maintain body temperature. The adaptive response of the circadian rhythm of liver metabolism to chronic cold exposure remains largely unexplored. Here, we investigated the circadian rhythm adaptation of hepatic metabolism in response to environmental cold stress using a mouse model of chronic cold exposure. We analyzed metabolites and transcripts of mouse livers at 24 h and found that long-term low-temperature exposure resulted in a synergistic and phase synchronization of transcriptional rhythms of many genes associated with metabolic pathways. Notably, transcription peaked in the early light phase when the body temperature was relatively low. Our results suggest that chronic cold does not alter the rhythmic expression of essential core clock genes in the liver, so the rewiring of clock control gene expression is another mechanism that optimizes the circadian rhythm of liver metabolism to meet the energy requirements of animal thermogenesis.